Rural Infrastructure and its Implication to Labor Market Participation in Jimma Zone, South-West Ethiopia - Chigeto, Amsalu Dachito; Haile, Minyahil Alemu (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2020)
Rural economy remain the back bone of Ethiopian economy absorbing tremendous labour share while how these labour market behave in rural economy of Ethiopia is yet uncovered. Besides the appreciated role of rural access to basic infrastructure with reference to rural labor supply decision, the topic is not bold in domestic literature. Considering this inadequate attention to the topic, we tried to examine the impact of rural infrastructure provision on individual labour supply, and assess the implication with each component of rural services to household participation decision in the labor market, using household survey from Jimma zone. Our multinomial logit regression indicated that rural services like education, health, credit, market information and access to all-weather-road are important considerations with regard to individual labor supply decision in farm and off-farm activities. It would be better to enhance rural access to efficient agricultural extension as well as other basic services towards empowering rural livelihood, and ensuring economic transformation at large.